Milk and Dairy Product Consumption Habits of University Students in Turkey - Guler, Hakan; Seker, Pınar; Köseman, Abdurrahman; Şeker, İbrahim (My University, 2021)
The aim of this study was to calculate the prevalence and changes in milk due to subclinical mastitis in Anatolian buffaloes, and the financial losses caused by the disease. The material of the study consisted of milk samples obtained from 96 udder lobes belonging to a total of 24 female Anatolian buffaloes raised in Kayseri. Milk samples were collected from four farms in March 2021 and the infection status of the milk was evaluated by examining the California Mastitis Test (CMT) and somatic cell count (SHS). According to the results, 5 buffalo (20.8%) and 8 lobes (8.3%) were found to be infected and mean SHS value was found as 182500 cell/ml. The fat of infected animals milk decreased by 27.4% (P<0.05) and the milk yield decreased by 12.6%, if the disease was not treated, it was calculated that a loss of 1140 TL (138 $) will occur in a lactation, and if treated, this loss can be reduced by 951.5 TL (115 $). In conclusion, it was revealed that the prevalence of subclinical mastitis in Anatolian buffaloes raised in Kayseri is high (20.08%), infection significantly reduces milk fat, especially in terms of quality, producers should educate in terms of diseases and pay more attention to hygiene, otherwise subclinical mastitis will cause significant losses and reduce their profitability.
Keywords: Habit; health; Dairy product; milk consumption; food safety